Essays in development economics: land rights, ethnicity and birth order - Collin, M (2012)
Aside from the introduction and conclusion, this thesis comprises four core chapters: The first chapter investigates the presence of endogenous peer effects in the adoption of formal property rights. Using data from a unique land titling experiment held in an unplanned settlement in Dar es Salaam, Tanzania. I show a strong, positive impact of neighbour adoption on the household’s choice to purchase a land title. I also show that this relationship holds in a separate, identical experiment held a year later in a nearby community, as well as in administrative data for approximately 45,000 land parcels in the same city. I also discuss possible channels, including the possibility of complementarities in the reduction in expropriation risk. The second chapter examines the relationship between ethnic heterogeneity and the demand for formal land tenure. Using a unique census of two highly fractionalised settle- ments in Dar es Salaam, I show that households located near coethnics are significantly less likely to purchase a limited form of land tenure recently offered by the government. I attempt to address one of the chief concerns, endogenous sorting of households, by con- ditioning on a households choice of neighbors upon arrival in the neighborhood. These results suggest that close-knit ethnic groups may be less likely to accept state-provided goods if they can generate reasonable substitutes. The third chapter is a short chapter which presents results from a recent policy experi- ment in Tanzania where formal land titles were provided to informal settlers at randomised prices. Land owners were also randomly assigned conditional discounts, which could only be applied if a woman was designated as owner or co-owner of the land in question. Results show that conditionality has no adverse effects on demand for land titles, yet drastically increases the probability a woman is included. We discuss the implications of these results for the expected bargaining power impacts of the intervention. The final chapter investigates birth order effects on both anthropometric and edu- cation outcomes in a longitudinal survey of children from the Philippines. Birth order effects are present early in life for both outcomes, but attenuate as children approach adulthood. There is also evidence for nonlinear birth order effects, with both firstborn and lastborn children holding an advantage over middleborn children. These results are at odds with prevalent theories of birth order which predict lasting and monotonic differences in outcomes across children.